Personal Finance - Siegel, Rachel; Yacht, Carol (Open textbook library., 2009)
Personal Finance by Rachel Siegel and Carol Yacht is a comprehensive Personal Finance text which includes a wide range of pedagogical aids to keep students engaged and instructors on track. This book is arranged by learning objectives. The headings, summaries, reviews, and problems all link together via the learning objectives. This helps instructors to teach what they want, and to assign the problems that correspond to the learning objectives covered in class. Personal Finance includes personal finance planning problems with links to solutions, and personal application exercises, with links to their associated worksheet(s) or spreadsheet(s). In addition, the text boasts a large number of links to videos, podcasts, experts' tips or blogs, and magazine articles to illustrate the practical applications for concepts covered in the text. Rachel would love to hear from you. If you have questions about teaching with her book, comments about teaching Personal Finance, or just feedback, feel free to email her at rachelsiegelcfa@hughes.net. This textbook has been used in classes at: Miami University.